2020
DOI: 10.3389/fneur.2020.00743
|View full text |Cite
|
Sign up to set email alerts
|

Management of Juvenile Myasthenia Gravis

Abstract: Juvenile Myasthenia Gravis (JMG) is a rare disorder, defined as myasthenia gravis in children younger than 18 years of age. While clinical phenotypes are similar to adults, there are a number of caveats that influence management: broader differential diagnoses; higher rates of spontaneous remission; and the need to initiate appropriate treatment early, to avoid the long-term physical and psychosocial morbidity. Current practice is taken from treatment guidelines for adult MG or individual experience, with cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
29

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 89 publications
(139 reference statements)
1
48
0
29
Order By: Relevance
“…Generalization of symptoms occurs less often compared to adult MG patients. Moreover, the rate of spontaneous remissions is much higher than in adults [ 55 , 56 , 57 ]. Similar to the adult-onset MG, AChR Ab are mostly detected in both ocular and generalized MG [ 55 , 58 ].…”
Section: Clinical Spectrum Of Mgmentioning
confidence: 99%
“…Generalization of symptoms occurs less often compared to adult MG patients. Moreover, the rate of spontaneous remissions is much higher than in adults [ 55 , 56 , 57 ]. Similar to the adult-onset MG, AChR Ab are mostly detected in both ocular and generalized MG [ 55 , 58 ].…”
Section: Clinical Spectrum Of Mgmentioning
confidence: 99%
“…Accurate antibodies detection is crucial for diagnosis and prognosis, together with other factors, such as thymus histology, age and clinical features. For instance, AChR antibody-positive patients tend to have follicular hyperplasia of the thymus and practically all cases of thymoma are AChRAbs positive, thus thymectomy (surgical removal of thymus) is a first-line treatment choice in AChR MG, excluding patients with only OMG ( 29 , 92 94 ). In addition, refractory AChR-MG is usually present in patients with thymoma.…”
Section: Implications For Therapiesmentioning
confidence: 99%
“…The disease has two typical peaks of onset; early-onset MG (EOMG, <50 years), with a predominance of females and late-onset MG (LOMG, >50 years), that have a larger proportion of males (18,24). In contrast, neonatal and juvenile MG is relatively uncommon and symptoms are usually less severe and limited to OMG form (18, [27][28][29][30]. Genetic studies have revealed strong relationship between human leukocyte antigen, HLA-DQA1, DQB1 with thymoma, while HLA-DQB1and DRB1alleles were associated with EOMG, LOMG and OMG (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile myasthenia gravis (JMG) is an autoimmune disorder with an immune response directed against the neuromuscular junction, whereas congenital myasthenic syndrome (CMS) refers to a group of genetic disorders affecting proteins expressed at the neuromuscular junction 1‐3 . Neonatal myasthenia gravis may occur in 10% to 20% of infants born to women with myasthenic syndrome (MG) due to transplacental transfer of acetylcholine receptor antibodies, but is not suitable for evaluation using the scales under investigation in this study 2,4 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Neonatal myasthenia gravis may occur in 10% to 20% of infants born to women with myasthenic syndrome (MG) due to transplacental transfer of acetylcholine receptor antibodies, but is not suitable for evaluation using the scales under investigation in this study. 2,4 JMG and CMS have fluctuating courses, although treatment can improve disease course and well-being of patients. 5 History and neurological examination at a single office visit is limited in assessing disease course and response to therapy due to recall bias, physician variability, and the variable symptoms of the disease.…”
mentioning
confidence: 99%